Impacto da assimilação de dados de sondagem e radiâncias em evento de ciclogênese - Alves, Leonardo Matias (2021)
An assessiment of the assimilation satelitte radiances and the atmospheric soundings impact in the WRF simulation is presented in this work. The simulation is performed during a cyclone propagation over southern Brazil, from August 20 to 23, 2020. The techinique used in this study is a Three-Dimensional Variational Data Assimilation Scheme implemented on WRF Model (3DVAR). The results show that the assimilation procedure has a higher impact on the first 48 hours of forecasting for low a medium level of the atmosphere. It was also concluded that 2-hour data assimilation window centered on the analysis time, presents a better result than larger windows. Aditional results show that errors of day matrix (B) generated by few forecasting pairs (24h -12h) presents worse results than the generic matrix provided by the WRF assimilation package. Lastly, it was show in this work that satellite data has a better impact than sounding data in the weather forecast on large scale.